Exploring PechaKucha in EFL learners’ speaking fluency - Hesti Rokhaniyah (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2019)
The research aims at investigating to what extent PechaKucha optimizes English as a foreign language (EFL) learners’ speaking fluency and identifying the class climate when learners implement PechaKucha. The data of the study were derived through classroom observation, pre and post-tests, field note, and interview. Constant Comparative Method was used to analyze the qualitative data while the mean score of two raters was found out to obtain the quantitative data. The result from this research indicated that the exploration of PechaKucha optimized EFL learners' speaking fluency including improving the speed of learners' speech and words per minute; increasing articulation rate; strengthening phonation time ratio; reducing the frequency of silent pause; avoiding filler words; and decreasing disfluency in spontaneous speech. The enhancement of learners’ score showed from the mean score of pre-test was 65.8; post-test 1 was 73.4, and post-test 2 was 82.3. The use of PechaKucha also improved the class climate: EFL learners were involved actively to present course material and their responsibilities to work in pair increased. Considering the research findings, it is suggested that teachers and lecturers implement PechaKucha for assisting the learners to enhance their speaking fluency and creating the effective class climate.